Notes on Early Land Plants Today. 15. Apotreubia hortoniae validated (Treubiaceae, Marchantiophyta) - Konstantinova, Nadezha A.; Söderström, Lars; Hagborg, Anders; Von Konrat, Matt (Phytotaxa, 2013)
When describing Apotreubia hortonae Schuster & Konstantinova (1995) failed to indicate the herbarium the type was deposited in. The original publication spelled the epithet "hortonae" whereas the proper Latin would be "hortoniae". These mistakes are corrected here.